Complicações Urológicas Pos-Wertheim-Meigs - Vianna, João B. (2023)
Amoni 78 Wertheim-Meigs operations for cancer of the cervix Perform the National Cancer Institute (Rio de Janeiro) 13 cases of urological complications occured. Each type of these complications is studied and urogramms made before and after the appearence of the urological lesion are shown from several patients.